2020
DOI: 10.1002/qj.3733
|View full text |Cite
|
Sign up to set email alerts
|

The role of secondary cyclones and cyclone families for the North Atlantic storm track and clustering over western Europe

Abstract: Secondary cyclones are those that form in association with a pre-existing primary cyclone, typically along a trailing cold front. In previously studied cases they have been shown to cause extreme damage across Europe, particularly when multiple cyclones track over the same location in rapid succession (known as cyclone clustering). To determine the dynamical relationship between primary and secondary cyclones over the North Atlantic, a frontal identification algorithm is partnered with a cyclone identification… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 80 publications
(163 reference statements)
2
25
0
Order By: Relevance
“…The third cyclone (C, purple) forms on the cold front of cyclone B in the eastern North Atlantic and also tracks over the British Isles. Following the genesis of a primary cyclone (A), the authors 59 have shown that RWB increases (upper level in Fig. 5), leading to an increase in jet speed and a decrease in low-level stability.…”
Section: Secondary Cyclogenesis and Cyclone Familiesmentioning
confidence: 98%
See 2 more Smart Citations
“…The third cyclone (C, purple) forms on the cold front of cyclone B in the eastern North Atlantic and also tracks over the British Isles. Following the genesis of a primary cyclone (A), the authors 59 have shown that RWB increases (upper level in Fig. 5), leading to an increase in jet speed and a decrease in low-level stability.…”
Section: Secondary Cyclogenesis and Cyclone Familiesmentioning
confidence: 98%
“…3), the RWB occurrences on both sides of the jet constrain its latitudinal variation. The largest RWB event typically corresponds to the first cyclone in a cyclone family (primary cyclone, see 'Introduction'), which sets up the environment for the following cyclones by contributing to a strengthening of the jet stream and reducing low-level stability 49,59 . The physical interpretation is that RWB enhances the thermal gradients at the jet level, thus accelerating the jet and leading to a downstream extension 60 , which ultimately foster the occurrence of the cyclone family.…”
Section: Jet Stream and Rwbmentioning
confidence: 99%
See 1 more Smart Citation
“…A second but less dense region is discernible in the Pacific off the US west coast, reminiscent of Kona lows (Simpson, 1952;Morrison and Businger, 2001;Moore et al, 2008). The downstream regions are eventually related to secondary or downstream cyclogenesis, though one would expect high EGR due to the trailing cold fronts typically involved in secondary cyclogenesis (Schemm and Sprenger, 2015;Schemm et al, 2018;Priestley et al, 2020). Over the Atlantic, this category also comprises the deepening of subtropical cyclones, which form under strong QGω forcing, provided by equatorward pushing intrusions of high-PV air (Caruso and Businger, 2006) and a weak baroclinic zone.…”
Section: Geographical Distribution Of Dry-dynamic Forcingmentioning
confidence: 99%
“…The typical CCW hurricanes hitting the U.S. move North from the Caribbean has its highest wind speeds and storm surge on the eastern side of it eye wall. Investigation of the shear zone identified with the diametric property (as seen in Fig 4) may be worthwhile for future investigations for the possible causes of strong side spawning of 2 nd order cyclones (34,35). The 2 nd order cyclones, or vortex shedding is evident in studies of Reynold's number, air turbulence and lift in the description of insect and avian flight (36,37).…”
Section: A the Diametric Property Of Rde And Sde -Rotational Relativitymentioning
confidence: 99%